2020
DOI: 10.1136/sextrans-2020-054756
|View full text |Cite
|
Sign up to set email alerts
|

Reduced sexual contacts with non-steady partners and less PrEP use among MSM in Belgium during the first weeks of the COVID-19 lockdown: results of an online survey

Abstract: ObjectivesTo examine changes in the occurrence of physical sex with non-steady partners among men who have sex with men (MSM) in Belgium during the first weeks of the COVID-19 lockdown and associations with sociodemographic factors, sexual practices, drug, alcohol and pre-exposure prophylaxis (PrEP) use. A secondary objective was to explore changes in PrEP use and the need for PrEP follow-up.MethodsA cross-sectional online survey. The questionnaire was available in Dutch, French and English, between April 10 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 23 publications
6
70
0
1
Order By: Relevance
“… 104 , 105 Other studies (but not all) have described substantial reductions in sex with non-steady partners during the first weeks of lockdown among men who have sex with men (MSM). 106 , 107 , 108 , 109 These studies describe MSM as indicating fewer sexual partners or fewer opportunities for having sex. Reduced sexual activity with sexual partners external to the household is more likely to result in reduced sexual transmitted infections among HIV-positive MSM.…”
Section: Monitoring Hiv Infection In Outpatient and Care Facilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“… 104 , 105 Other studies (but not all) have described substantial reductions in sex with non-steady partners during the first weeks of lockdown among men who have sex with men (MSM). 106 , 107 , 108 , 109 These studies describe MSM as indicating fewer sexual partners or fewer opportunities for having sex. Reduced sexual activity with sexual partners external to the household is more likely to result in reduced sexual transmitted infections among HIV-positive MSM.…”
Section: Monitoring Hiv Infection In Outpatient and Care Facilitiesmentioning
confidence: 99%
“…Reduced sexual activity with sexual partners external to the household is more likely to result in reduced sexual transmitted infections among HIV-positive MSM. 106 A Belgian study described MSM who had sex with nonsteady partners were significantly more likely to be HIV positive, to use pre-exposure prophylaxis (PrEP), or to have engaged in sexual practices such as group sex, chemsex, and sex work, before the first national lockdown, compared with their counterparts. 106 Lockdown restrictions and reducing in-person visits during the COVID-19 pandemic might have interrupted both pre-exposure prophylaxis for adults at high-risk of HIV infection and antiretroviral treatment for people living with HIV.…”
Section: Hospital Wardmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in LD1, an online survey indicated that Belgian MSM reduced their sexual activity with nonsteady partners with 85%. 7 Although no Belgian sexual activity data are available for LD2, personal communication with patients indicate regular sexual activity through internet dating and in private encounters during this period, despite the social measures and the threat of being fined by the authorities.…”
Section: Discussionmentioning
confidence: 99%
“…6 Furthermore, a reduction in casual sex was noted in several countries, including Belgium, during the first lockdown. 5,[7][8][9] However, few studies are available which investigate the trend of STIs after a lockdown period, and to our knowledge, none of them explored the effect of the mitigating efforts of the second COVID-19 wave in Europe.…”
Section: Introductionmentioning
confidence: 99%